English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

use substitution to solve each system of equations. check the solution?
please help summer practice

2007-06-23 14:27:15 · 3 answers · asked by king 1 in Science & Mathematics Mathematics

3 answers

Hi,

7.) y+2x=11
x+y=5

Solving the first equation for y, y = 11 - 2x. Substituting that into the second equation, it becomes:

x+y=5
x+11-2x=5 Simplify this:
-x+11=5
-x =-6
x=6
If x = 6, then x+y=5 becomes 6+y=5, so y = -1

FIRST ANSWER: (6,-1)

8.) x-10y=2
x-6y=6

Solving the first equation for x, x = 10y+2. Substituting that into the second equation, it becomes:

x-6y=6
10y+2-6y = 6
4y+2 = 6
4y = 4
y = 1

If y = 1 is substituted into x-6y=6, it becomes: x -6(1) = 6 or
x - 6 = 6, so x = 12. The answer is (12,1). <== answer

9.) 8x=y
2x+y=5

Since y = 8x, 8x can be substituted into the second equation for y to make it:

2x+y=5
2x+8x=5
10x=5
x=½

If we substitute that back into y = 8x, then y = 8(½) or y = 4.

The answer is (½,4).



I hope that helps!! :-)

2007-06-25 14:25:48 · answer #1 · answered by Pi R Squared 7 · 0 0

Question 7
y = 11 - 2x
x + (11 - 2x) = 5
- x + 11 = 5
- x = - 6
x = 6
y = - 1

Question 8 (guessing x - 10y = 2?)
x = 6 + 6y
6 + 6y - 10y = 2
-4y = - 4
y = 1
x = 12

Question 9
2x + 8x = 5
10x = 5
x = 0.5
y = 4

2007-06-27 17:52:11 · answer #2 · answered by Como 7 · 0 0

Okay, basically you isolate one variable in each problem and substitute it to find the answer.
For example, for number 7, you can subtract y from both sides in the second equation to get x=5-y. Now that you know what x is, you can substitute it in the first equation to get y+2(5-y)=11, which, after all the distributing and subtracting, gets you y=-1. Now, you can use that in the second equation, substitute y for -1 to get x-1=5, and so x=6.
Now you just apply that principle to the next two problems. =D
Hope that helped...

2007-06-23 21:38:19 · answer #3 · answered by Jenniferr. 2 · 0 0

fedest.com, questions and answers